Trunk scales as a predictor of Gait in Stroke Patients- A Systematic Review - Sejal, Labhane; Suvarna, Ganvir (VIMS JOURNAL OF PHYSICAL THERAPY, 2025)
Background: Trunk control is known to be an early predictive factor for one’s ability to perform activities of daily living (ADL) as well as the hospitalization period in stroke survivors. Gait disturbance is a major problem for many patients after stroke and causes difficulties in performing daily activities. are tools for assessing trunk control, such as the Trunk Impairment Scale (TIS), Trunk Control Test (TCT), Postural Assessment Scale for Stroke-Trunk Control (PASS-TC). These scales have not been used to predict gait independence. Objective: To find out if trunk scales predict gait independence in patients of stoke Data Sources: The biomedical databases CINAHL, Cochrane, Scholar and PubMed were searched. Each database was searched until 2024 . Review Methods: The four databases were searched with the terms plus ‘stroke’ and ‘trunk’ plus ‘scale’ and ‘Gait’ mentioned in the title or abstract. The search strategy included all studies in humans with original data from adults after stroke. All articles were selected for this review which reported or included a clinical measure of trunk performance. Only articles that were published in English were included. Result: After screening of 367 studies, 9 studies met the inclusion criteria. The mean PEDro score was 6 out of 10 which corresponds with a low risk of bias. Conclusion: Prediction of gait independence can be done using trunk scales such as Trunk Impairment Scale (TIS), Ability for Basic Movement Scale II (ABMS II), Trunk Control Test (TCT), in patients with stroke.